Computational Study of Gas-Solid, Two-Phase Interaction System and Particle Kinetics Establishing 3D Analysis - Maisa El Gamal; Ameera Mohammad; Basim Abu-Jdayil; Imen Ben Salem (Results in Engineering)
This study explores gas-solid contact systems, specifically fluidized beds, crucial in various industries. The focus is understanding their 3D model, hydrodynamics, and particle interactions among changing gas flow conditions. Utilizing a Computational Fluid Dynamics (CFD) model with the Eulerian method, the research navigates the complexities of multiphase and turbulent flows. The approach employs distinct equations for each phase, facilitating interaction within the computational domain. Turbulence effects are incorporated through the realizable k–ε model, known for its precision in representing turbulent behaviors in multiphase flow. The investigation investigates the complex interactions between phases using the continuity equation, emphasizing mass conservation with mass transfer terms capturing substance movement between phases. The Discrete Phase Model (DPM) is integral in understanding particle behavior, employing massless inert particles for targeted insights into system behavior and gas-solid interaction. Observations reveal that introduced particles have a limited impact on pressure dynamics, a crucial aspect of reactor design and optimization. The study explores the influence of varying gas and particle velocities on system pressure, turbulence kinetic energy, and particle distribution within the reactor. Results show minimal effects on pressure dynamics due to changes in particle velocity, with system pressure ranging from 0.33 Pa at the lowest air velocity of 0.5 m/s to 12.08 Pa at the highest air velocity of 3 m/s, establishing a nearly linear relationship between air velocity and pressure. The research extends to experimental validation, showing commendable agreement with computational findings. While empirical investigations are in preliminary stages, they promise further research optimization. This study provides a comprehensive understanding of gas-solid contact systems, emphasizing the importance of precise control over air and particle velocities for optimal system performance. The findings carry practical implications across diverse industrial applications and suggest avenues for continued research and development.